Unmet Health Needs of Roma Women in the Two Biggest Roma Communities in the Republic of Srpska, Bosnia and Herzegovina - Stojisavljevic, Stela; Grabez, Milkica; Stojanovski, Kristefer (Frontiers in Public Health, 2020)
Background: Reasons for unmet health needs vary from individual to contextual determinants but are defined as the difference between needed health service and services actually received. Roma experience elevated health issues and challenging social conditions. Objective: The aim of this study was to explore the unmet health needs and potential risk factors among Roma women living in the two biggest Roma communities in the Republic of Srpska. Method: We conducted a health assessment of 183 adult Roma women in the Republic of Srpska. Unmet health needs were observed as the absence of needed medical supervision, despite having chronic conditions. We used logistic regression to assess the degree to which unmet health needs were related to the social determinants and the health status of Roma women. Results: The majority of Roma women were married or were in an unofficial relationship (55.2%), were without schooling (62.8%), and were unemployed (88.5%). The results showed that 94.0% had health insurance, had a health card, and were registered with a family medicine doctor. Sixty percent reported having a chronic disease; however, 68.2% reported that their chronic disease was not medically supervised. Roma women that had less education, those who were unemployed, and those who were divorced or widowed women were more likely to have unmet health needs. Conclusion: Roma women in Bijeljina and Prijedor have unmet health needs due to the circumstances they live in despite the fact that majority of them have health insurance and universal health access is legally guaranteed.